2015
DOI: 10.1155/2015/409286
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of R&D Cooperation in a Supply Chain

Abstract: R&D outsourcing becomes the often-adopted strategy for firms to innovate. However, R&D cooperation often ends up with failure because of its inherent quality of instability. One of the main reasons for cooperation failure is the opportunistic behavior. As the R&D contract between firms is inherently incomplete, opportunistic behavior always cannot be avoided in the collaborative process. R&D cooperation has been divided into horizontal and vertical types. This paper utilizes game theory to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Dickson et al [18] empirically analyzed the effects of opportunism on the R&D alliances of small-to medium-sized enterprises (SMEs) with samples from eight countries. Xu et al [19] studied opportunistic behaviors in vertical R&D using game theory, and proved the inherent instability of vertical R&D, since downstream firms are more likely to break the agreement. Conti and Marini [20] found that information asymmetry may exacerbate underinvestment without R&D agreements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dickson et al [18] empirically analyzed the effects of opportunism on the R&D alliances of small-to medium-sized enterprises (SMEs) with samples from eight countries. Xu et al [19] studied opportunistic behaviors in vertical R&D using game theory, and proved the inherent instability of vertical R&D, since downstream firms are more likely to break the agreement. Conti and Marini [20] found that information asymmetry may exacerbate underinvestment without R&D agreements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The advantage of one of the above models of vertical R&D over the others turned out to depend on the value of knowledge spillovers in the industry. Xu, Liang, Duan, and Xiao (2015) use the analytical framework developed by Kamien et al (1992) to formally show that vertical R&D cooperation is unstable, as the downstream firm is more likely to break the cooperation agreement. Therefore, when establishing R&D cooperation, firms must carefully consider the reputation of potential partners and the extent of trust between the firms operating in the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…+ < 1 represents the decreasing returns to scale, or decreasing marginal utility of R&D investment. In other words, with the increase of R&D investment or the technical level, the increment of technical level from the same R&D investment decreases, or we should make more R&D investment to obtain the same increment of technical level [22].…”
Section: Problem Description and Thementioning
confidence: 99%